A Randomized Waitlist Controlled Analysis of Team-Initiated Problem Solving Professional Development and Use. (August 2018) - Horner, Robert H.; Newton, James S.; Todd, Anne W.; Algozzine, Bob; Algozzine, Kate; Cusumano, Dale; Preston, Angela
Data-based problem solving is a hallmark of research-supported practices such as positive behavioral interventions and supports. In this study, we provided members of positive behavioral interventions and supports (PBIS) teams from 38 elementary schools with professional development focused on a research-supported problem-solving model (Team-Initiated Problem Solving). We used direct observations to document procedures, practices, and outcomes before and after participating in the professional development workshop. Within the context of a randomized waitlist controlled trial, team members in the Immediate Group demonstrated greater improvement in (a) problem-solving procedures, (b) decision-making practices, and (c) meeting outcomes than did members of PBIS teams in the Waitlist Group. Our findings extend what is known about team-based problem solving and provide a framework for future research and improved practice related to decision making by school teams.